Experiences of the COVID-19 pandemic: A survey of patients on home parenteral nutrition. (August 2022) - McCulloch, Adam; Jones, Ilva; Fletcher, Jane; Malhi, Hardip; Cooper, Sheldon C.
Summary: Patients on home parenteral nutrition (HPN) have had to endure sweeping changes to their personal lives and medical care during the COVID-19 pandemic. We evaluated the patients' perspectives of these changes at our Intestinal Failure/Rehabilitation centre in order to initiate a debate on improving HPN care. The findings point to high levels of anxiety and depression amongst the 35 patients surveyed with many reporting frustration at conflicting information from different sources. Telephone consultations were well received and most were keen for these to continue. In light of these results, we outline recommendations to enhance our patients' experiences in the coming phases of the pandemic.